Validity and reliability of the athlete diet index in Turkish athletes - Uçak, Merve Nur; Bilgic, Pelin; Öztürk, Ebru (Frontiers in Nutrition, 2026)
IntroductionThis study aimed to assess the diet quality of Turkish athletes and confirm the validity and reliability of the Athlete Diet Index (ADI), which is the only index designed to assess diet quality in athletes. The ADI assesses three primary domains: basic athlete nutrition, nutrition for exercise performance, and personal dietary practices.MethodsThe final Turkish version of the ADI, developed through forward–backward translation (n = 5 + 2), expert review (n = 10), and a pilot study (n = 15), was administered to 151 professional athletes. Construct validity was examined by assessing the association between ADI scores and 2-day food record scores. Test–retest reliability was evaluated by readministering the ADI to 44 athletes after 3 weeksResultsAll assessments were conducted face-to-face. The ADI demonstrated strong validity (r = 0.798, p < 0.001) and good test–retest reliability (ICC = 0.79, 95% CI). Diet quality did not differ by age, sex, or individual versus team sport (p > 0.05); however, athletes competing in weight-category sports had significantly lower diet quality than non-weight-category athletes (p = 0.01).ConclusionThe ADI is valid and reliable tool for evaluating the diet quality of Turkish athletes and can be confidently used in both research and applied sports nutrition settings.